Mutations of RAS genes identified in acute myeloid leukemia affect glycerophospholipid metabolism pathway - Liang, Tianqi; Kong, Yanxiang; Xue, Hongman; Wang, Wenqing; Li, Chunmou; Chen, Chun (Frontiers in Oncology, 2023)
Background Acute myeloid leukemia (AML) is a malignant disease originating from myeloid hematopoietic stem cells. Recent studies have shown that certain gene mutations promote tumor cell survival and affect the prognosis of patients by affecting metabolic mechanisms in tumor cells. RAS gene mutations are prevalent in AML, and the RAS signaling pathway is closely related to many metabolic pathways. However, the effects of different RAS gene mutations on AML cell metabolism are unclear. Objectives The main purpose of this study was to explore the effect of RAS gene mutation on the metabolic pathway of tumor cells. Methods In this study, we first used a retrovirus carrying a mutant gene to prepare Ba/F3 cell lines with RAS gene mutations, and then compared full-transcriptome data of Ba/F3 cells before and after RAS gene mutation and found that differentially expressed genes after NRASQ61K and KRASG12V mutation. Results We found a total of 1899 differentially expressed genes after NRASQ61K and KRASG12V mutation. 1089 of these genes were involved in metabolic processes, of which 167 genes were enriched in metabolism-related pathways. In metabolism-related pathways, differential genes were associated with the lipid metabolism pathway. Moreover, by comparing groups, we found that the expression of the DGKzeta and PLA2G4A genes in the glycerophospholipid metabolism pathway was significantly upregulated. Conclusion In conclusion, our study revealed that RAS gene mutation is closely related to the glycerophospholipid metabolism pathway in Ba/F3 cells, which may contribute to new precision therapy strategies and the development and application of new therapeutic drugs for AML.